Shift of Form and Meaning in The Translation of Bilal Animation Film Subtitle: “A New Breed of Hero (2015)” - Fernanda Venturini Nur Salimova, Abdul Malik (CMES (Center of Middle Eastern Studies), 2020)
This article will generally examine the translation shift of form and meaning of the subtitle animated film Bilal: A New Breed of Hero (2015) works by Ayman Jamal with duration 1 hour 51 minutes 43 seconds. The approach used in this study is describing the form and meaning shifting of the translation used by the translator in translating its film. The research method is qualitative descriptive method. The source of the data in the film: Bilal (2015) and the subtitle. Data collection was performed by the method of non-interactive form of observation by exploring in general the film along with the subtitle translation, then the observation is focused with a narrow aspect of translation shift in form and meaning. The research showed that from 297 data, there are 3 types of shift forms, namely 77 data shift at the level of the morpheme, 53 data shift in word category, and 115 data shift at the level of syntax. As for the shift in meaning, there are 3 types, namely 16 data from the generic meaning to the specific, 13 data from the specific meaning to the generic and 23 data shift according to the cultural point of view.